2022
DOI: 10.1039/d2ce01301k
|View full text |Cite
|
Sign up to set email alerts
|

A Keggin-type polyoxomolybdate-based crystalline material formed by hydrothermal transformation: photo/electro-catalytic properties and mechanism study

Abstract: This study constructs a POM-based crystalline material of [(SiMo12O40)Cu6(2,2′-bipy)6(Mo6O22)] (1). The photocatalytic MB degradation and electrocatalytic nitrite reduction properties of complex 1 are systematically studied for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In particular, these materials can be used for chemical energy conversion, storage, and fuel production via electroor photo-electro-catalytic methods. In addition, some emerging application areas in organic light-emitting diode/organic photovoltaics (OLED/OPVs) [192,193], water purification [194,195], mechanism studies [196], semiconductors, and 3D printing [197,198] have been reported based on recent pioneering studies on POMs.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…In particular, these materials can be used for chemical energy conversion, storage, and fuel production via electroor photo-electro-catalytic methods. In addition, some emerging application areas in organic light-emitting diode/organic photovoltaics (OLED/OPVs) [192,193], water purification [194,195], mechanism studies [196], semiconductors, and 3D printing [197,198] have been reported based on recent pioneering studies on POMs.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…These compounds exhibit an impressive open nanocluster structure, multi‐electron redox properties, and stability in their cluster structure throughout reduction‐oxidation processes. These characteristics make them highly promising for a range of applications in various catalytic reactions [36–37] and electrocatalysis, [38–39] and other electrochemical reactions [40–58] . In 2018, Dong, Cronin, and their co‐workers developed a dual‐function Lewis acid and base catalyst for Li−S batteries in the form of an Ag(I)‐substituted Keggin K 3 [H 3 AgIPW 11 O 39 ] cluster.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make them highly promising for a range of applications in various catalytic reactions [36][37] and electrocatalysis, [38][39] and other electrochemical reactions. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] In 2018, Dong, Cronin, and their co-workers developed a dual-function Lewis acid and base catalyst for LiÀ S batteries in the form of an Ag(I)-substituted Keggin K 3 [H 3 AgIPW 11 O 39 ] cluster. LiPSs can be strongly adsorbed on the {AgIPW 11 O 39 } cluster.…”
Section: Introductionmentioning
confidence: 99%